Redox-induced formation and cleavage of O-O sigma and pi bonds in a peroxo-bridged manganese dimer: A density functional study - McGrady, J; Stranger, R (1999)
The structural and electronic consequences of reduction and oxidation of a peroxo-bridged Mn2IV/IV dimer, Mn2(μ-O)2(μ-O2)(NH3) 62+, are examined using approximate density functional theory. In both cases, the initial electron-transfer step is localized on the metal centers, but subsequent structural rearrangement results in transfer of the excess charge to the μ-O2 unit, with concomitant regeneration of the Mn2IV/IV core. Two-electron reduction results in population of the O-O σ* orbital and complete cleavage of the O-O bond, whereas two-electron oxidation depopulates the O-O π* orbital, forming molecular oxygen. The coupling between the metal centers (antiferromagnetic or ferromagnetic) affects the stability of the intermediate species, in which the redox process is metal based, and hence influences the kinetic barrier to bond formation or cleavage. Reductive cleavage of the O-O σ bond is favored when the metal centers are antiferromagnetically coupled, whereas oxidative formation of the π component of the O-O bond is favored by ferromagnetic coupling. The possible implications for the relationship between structure and function in the oxygen-evolving complex found in photosynthetic organisms are discussed. © 1999 American Chemical Society.